2014
DOI: 10.1017/jsc.2014.12
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Interventions for Racial/Ethnic-Minority Pregnant Smokers

Abstract: Introduction Large disparities exist in smoking rates during pregnancy by racial/ethnic status. Aims The current review examined controlled studies that predominantly included racial/ethnic-minority pregnant smokers for providing smoking cessation treatment. Methods Two authors independently conducted the literature searches in the standard databases using a combination of the keywords with minority, pregnancy, smoking, and cessation identifiers. Results The searches identified nine articles that met the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 103 publications
(196 reference statements)
0
10
0
Order By: Relevance
“…Native Hawaiians and Filipinos were found in a previous study to have lower knowledge and use of cessation methods and products than Caucasians, suggesting that these groups may be underserved [48]. Tobacco companies have specifically targeted Asian immigrants and Asian Americans [49], while few interventions have been directed towards these communities [32]. To address this gap, the Centers for Disease Control and Prevention’s “Racial and Ethnic Approaches to Community Health” (REACH) project was launched to reduce racial/ethnic community health disparities using community-driven anti-smoking strategies [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Native Hawaiians and Filipinos were found in a previous study to have lower knowledge and use of cessation methods and products than Caucasians, suggesting that these groups may be underserved [48]. Tobacco companies have specifically targeted Asian immigrants and Asian Americans [49], while few interventions have been directed towards these communities [32]. To address this gap, the Centers for Disease Control and Prevention’s “Racial and Ethnic Approaches to Community Health” (REACH) project was launched to reduce racial/ethnic community health disparities using community-driven anti-smoking strategies [40].…”
Section: Discussionmentioning
confidence: 99%
“…National surveillance data based on self-report showed variability in prenatal smoke exposure patterns between different race/ethnic groups, with the highest rates of prenatal smoking in American Indian/Alaskan Native women, followed by white and African American women, and lower rates in Hispanics and Asians [31]. Using broad race/ethnic categories can obscure differences between subgroups [32], and federal data collection standards for race categories have been found to mask heterogeneity in smoking patterns [33]. Although Asians are the fastest growing race/ethnic group in the U.S. [34], studies of smoking patterns have categorized Asian/Pacific Islander as a single group or more typically been limited to white, African-American and sometimes Hispanic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Ten papers (Table 4) described the effectiveness of interventions for smoking cessation among pregnant women [47,[56][57][58][59][60][61][62][63][64]. Interventions included behavioral interventions such as contingency management (incentive-based treatment such as financial rewards), counselling, health education, social support, culturally tailored interventions and bio-feedback during ultrasound and pharmacotherapy for smoking cessation such as bupropion and nicotine replacement therapy.…”
Section: Interventions To Reduce Tobacco Exposure In Pregnancymentioning
confidence: 99%
“…Racial and ethnic minorities may benefit from psychosocial interventions such as counselling, brief advice and NRT [62]. However, in a review of culturally tailored smoking cessation interventions targeted at pregnant Indigenous women, Passey et al included two studies; neither study showed any significant effect compared to the control [61].…”
Section: Behavioral Interventionsmentioning
confidence: 99%
“…[14][15][16] Despite the identified need for research on strategies for decreasing smoking while pregnant among Indigenous women, 17 very few interventional studies have focused on this population. A systematic review by Washio and Cassey 18 identified only one study 19 and we have identified four more. [20][21][22][23] Other research has assessed knowledge and attitudes to smoking among pregnant Indigenous women.…”
Section: Introductionmentioning
confidence: 99%